2020
DOI: 10.47162/rjme.61.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Saccular function evolution related to cochlear implantation in hearing impaired children

Abstract: Vestibular sensorial input is essential for psychomotor development of the very small children. In consequence, possible vestibular impairment induced by cochlear implantation in deaf children could affect the balance and walking learning process. Some of cochlear implanted children can present congenital vestibular deficit. The anatomical and embryological relation between auditory and vestibular system explains why congenital neurosensorial hearing loss may associate vestibular impairment. The cochlear impla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…It is noteworthy that the approach of electrode insertion and the electrode type caused a difference in the incidence of CI-induced negative effect on caloric test and rotation test but not on cVEMP. Our results are compatible with previous studies that showed no significant differences in cVEMP between electrode types (44) and between approaches of electrode insertion (22).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It is noteworthy that the approach of electrode insertion and the electrode type caused a difference in the incidence of CI-induced negative effect on caloric test and rotation test but not on cVEMP. Our results are compatible with previous studies that showed no significant differences in cVEMP between electrode types (44) and between approaches of electrode insertion (22).…”
Section: Discussionsupporting
confidence: 93%
“…Reduction in caloric response and damped rotation response was more frequently observed in patients who underwent cochleostomy, and use of a perimodiolar electrode more frequently caused deterioration of caloric response compared with the use of a straight electrode. Previous studies have demonstrated that CI has a significant negative effect on the results of caloric and cVEMP test results in adults (5) and children (22). A wide range of rates of negative effects has been reported in caloric test (0-30%) (23,24) and cVEMP test (20-100%) (25)(26)(27), and cochleostomy has also been identified as a risk factor for loss of vestibular function in adults (9).…”
Section: Discussionmentioning
confidence: 99%
“…Also, higher rates of postoperative vestibular loss in literature might be related to the use of different surgical techniques. Although literature on this matter is still inconclusive, some studies indicate that cochleostomy might be more traumatic for the vestibular apparatus than the round window approach, the latter being applied for all subjects in our study (Todt et al 2008; Tsukada et al 2013; Cozma et al 2020). Three recent studies reported cVEMP measurements in children after CI surgery with round window approach (Ajalloueyan et al 2017; Cozma et al 2020; Li and Gong 2020).…”
Section: Discussionmentioning
confidence: 89%
“…Although literature on this matter is still inconclusive, some studies indicate that cochleostomy might be more traumatic for the vestibular apparatus than the round window approach, the latter being applied for all subjects in our study (Todt et al 2008; Tsukada et al 2013; Cozma et al 2020). Three recent studies reported cVEMP measurements in children after CI surgery with round window approach (Ajalloueyan et al 2017; Cozma et al 2020; Li and Gong 2020). With 27% (12/45) postoperative losses, Cozma et al (2020) reported a remarkably larger proportion of saccular loss in their round window subgroup compared to our study.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation